Does Entrepreneurs’ Darwinian Social Identity Contribute to Business Performance via Corporate Social Responsibility in China? The Role of Entrepreneurs’ Well-Being - Chen, Jinliang; Chen, Ning Chris; Yu, Kangkang; Hall, Colin Michael (Frontiers in Psychology, 2021)
Although the impact of entrepreneurs’ social identity on successful entrepreneurship has attracted much scholarly attention, it is often to evaluate successful entrepreneurship through direct channel to financial performance. Recently, there is a growing body of researches beginning to pay attention to the impact of entrepreneurs’ social identity on corporate social responsibility (CSR) regarded as indirect social aspect channel to successful entrepreneurship. However, little is known regarding how entrepreneurs’ Darwinian social identity affects CSR, which in turn, affects business performance. This study addresses this issue by combining stakeholder theory with social identity theory, to investigate the relationship between entrepreneurs’ Darwinian social identity and business performance via CSR. In addition, the moderating effect of entrepreneur’s well-being is further examined to uncover the interaction effect of the individual psychological resource on business performance. The empirical results indicate that entrepreneurs’ Darwinian social identity contributes positively to CSR, so as further to business performance. In addition, this relationship is further found to be significantly moderated by entrepreneurs’ well-being. The results indicate that entrepreneurs can achieve business success via CSR, by which entrepreneurs can further acquire successful entrepreneurship through caring more about their well-being.